Nothing in evolution makes sense except in the light of code biology - Prinz, Robert (BioSystems, 2023)
This article highlights the potential contribution of biological codes to the course and dynamics of evolution. The concept of organic codes, developed by Marcello Barbieri, has fundamentally changed our view of how living systems function. The notion that molecular interactions built on adaptors that arbitrarily link molecules from different “worlds” in a conventional, i.e., rule-based way, departs significantly from the law-based constraints imposed on livening things by physical and chemical mechanisms. In other words, living entities and non-living things behave like rules and laws, respectively, but this important distinction is rarely considered in current evolutionary theory. The many known codes allow quantification of codes that relate to a cell, or comparisons between different biological systems and may pave the way to a quantitative and empirical research agenda in code biology. A starting point for such an endeavour is the introduction of a simple dichotomous classification of structural and regulatory codes. This classification can be used as a tool to analyse and quantify key organising principles of the living world, such as modularity, hierarchy, and robustness, based on organic codes. The implications for evolutionary research are related to the unique dynamics of codes, or 'Eigendynamics' (self-momentum) and how they determine the behaviour of biological systems from inside, whereas physical constraints are imposed mainly from outside. A speculation on the drivers of macroevolution in light of codes is followed by the conclusion that a meaningful and comprehensive understanding of evolution depends on including codes into the equation of life.